AKULTURASI ISLAM DAN BUDAYA DALAM PROSESI PEMAKAMAN - Ainun Wardatul Hasanah; Mawarni Azzahra (CV. ADIBA AISHA AMIRA, 2023)
After Islam was born or entered Indonesia, the most dominant culture was Islamic culture. Indonesia is known for its cultural diversity and rich local traditional values, thus attracting much interest from researchers both locally, nationally and internationally. Apart from that, generally in this burial process there will be a separate procedure adopted by the community. Both based on religious rules, customs rules, and so forth. Traditions and customs arise and develop along with the mindset of the community. In the process of cultural growth it often creates interactions within community groups. Using qualitative research with descriptive writing and getting results, basically these traditions do not violate religious values, or these traditions are a belief in prayer through actions that are believed to make good deeds for those who do them and hopes as help for those who die. However, there are differences, one of which is for the brobosan tradition, it depends on the host or the person entrusted to the house, according to the local community, this sentence is a migrant community